Analisis Pengendalian Kualitas dan Pengembangan Produk Wafer Osuka dengan Metode Six Sigma Konsep DMAIC dan Metode Quality Function Deployment di PT. Indosari Mandiri - Didik Sutiyarno; Chriswahyudi Chriswahyudi (Universitas Bunda Mulia, 2019)
PT. Indosari Mandiri is an industrial company engaged in the manufacture of snacks. Problems that are being faced by PT. Indosari Mandiri is currently the number of defective products in flat wafer products, especially in Osuka wafer products. The number of product defects in the production process for one shift is an average of 30%. The current defect condition is very far from the tolerance of company defects which is 15%. To overcome these problems, Six Sigma methods are used. Six Sigma consists of Define, Measure, Analyze, Improve and Control (DMAIC). In the Define stage, the wafer osuka production process is defined and the Critical to Quality (CTQ) is determined. From the CTQ identification, there are several types of defects in the product, each of which is tough, the sheet is not full, dirty, broken, broken and peeled off. In the Measure stage, Six Sigma is calculated and determine the sigma level. In the Analyze stage, analysis of defect selection is done with a causal diagram or fishbone diagram, and the most dominant defects obtained are in the Creaming and Cutting section. The Improve stage is done by the Quality Function Deployment (QFD) method, to listen to the voices of loyal consumers of Osuka Wafer products. At the control stage, the input is only given to the company regarding the quality improvement of the osuka wafer product so that defective products can be suppressed. In this study it was concluded that improvements in the creaming and cutting process area need to be done immediately, in line with the QFD method that requires repairs to the area to improve or meet consumer desires.